Spleen Contraction During Sudden Eupneic Hypoxia Elevates Hemoglobin Concentration - Pernett, Frank; Schagatay, Felix; Vildevi, Caroline; Schagatay, Erika (Frontiers in Physiology, 2021)
The spleen contracts progressively during moderate normobaric hypoxia exposure of 20 minutes, which elevates hemoglobin concentration (Hb). However, acute hypoxia exposure could be shorter and more severe when oxygen systems fail during e.g., high-altitude sky diving, aircraft cabin pressure drop, balloon flights, extreme altitude climbing and in some maladies. Our aim was to evaluate the speed and magnitude of spleen contraction during short exposure to extreme eupneic hypoxia, and its subsequent recovery on oxygen. Eight female and seven male volunteers were exposed to normobaric hypoxia (10% oxygen) for 10 min during sitting rest, followed by 10 min on 100% oxygen. Heart rate (HR), arterial oxygen saturation (SpO₂) and mean arterial blood pressure (MAP) were measured continuously. The spleen was measured via ultrasonic imaging every minute for volume calculations and venous blood samples were drawn before and after exposure for hemoglobin concentration (Hb). Mean (SD) spleen volume was 279 (115) mL before exposure, 219 (75)mL (21% reduction; P=0.005) at 3 min of exposure, and 201 (93) mL after 10 min exposure to hypoxia (28% reduction; P < 0.001). Hb was 138.8 (7.6) g.L-1 before and 142.9 (8.1) g.L-1 after exposure (2.9 % increase; P < 0.001). SpO2 was 96.4 (1.7) % before exposure and 74.7 (8.4) % during the last minute of exposure (22.5 % reduction; P < 0.001). HR increased from 80 (14) to 90 (17) bpm during exposure (12% increase, P < 0.05). MAP remained unchanged. After 10 min recovery on oxygen, values had been restored for spleen volume and Hb, while SpO2 was higher and HR lower compared to before hypoxia exposure. We concluded that acute normobaric hypoxia of only 10 minutes caused significant spleen volume contraction with Hb increase. This rapid spleen response, evident already after 3 minutes of exposure, could have a protective effect during sudden exposure to severe hypoxia.